Ancient Greek Personal Names. Part I: Theory - Szefliński, Waldemar (Sensus Historiae, 2020)
The article discusses ancient Greek anthroponyms of the Classical period from a social and typological perspective. The former touches upon ancient Greek name giving practices, the number of names a Greek would bear and their general type. The latter focuses on a number of name characteristics such as male / female, theophoric / non-theophoric, simple / compound, derivative / non-derivative, derivative / compound, semantically easily interpretable / semantically harder to interpret, given name / diminutive (hypocoristic). The text is meant as a form of introduction to a ‘case study’ of Aristophanic anthroponymy to be presented in one of the author’s subsequent articles.